Towards a common vision of climate security in Guatemala - Madurga Lopez, Ignacio M.; Medina, Leonardo; Penel, Charlotte; Castellanos, Andrea; Surama Borrayo, Andrea; Hernandez, Monica Paola; Kenduiywo, Benson; Olivet, Francisco; Hernandez, Manuel A.; Castañeda Oajaca, Abbie Annette; Hernández Vela, Héctor René; Escobar López, Nasly Anabely; et al. (2023)
CGIAR’s Climate Resilience Initiative, also known as ClimBeR, is working to address these needs. On the 21st and 22nd of February, we ran in Guatemala City the first climate security workshop in Central America: Towards a common vision on the relationship between climate, conflict, and human security in Guatemala. The workshop was organized by the Alliance of Bioversity and CIAT along with the CGIAR’s Climate Resilience Initiative; the Fragility, Conflict, and Migration Initiative; the regional integrated initiative AgriLAC Resiliente; and the CGIAR FOCUS Climate Security and benefited from the participation of 45 individuals from 20 different organizations, including regional & local organizations, government institutions, UN agencies, and national universities